Polymeric ultralong organic phosphorescence with excellent humidity and temperature resistance via hydrophobic effect - Zhongyu Li; Kexin Fu; Huangjun Deng; Kaixuan Nie; Zhe Pan; Zhu Mao; Juan Zhao; Gang Li; Pengli Zhu; Zhenguo Chi; Rong Sun (Aggregate, 2024)
Abstract Polymeric ultralong organic phosphorescence (UOP) with persistent emission is of great importance in practical applications. However, achieving good water‐resistance for long‐term environmental stability is a formidable challenge. In this contribution, through tailoring the alkyl‐chain length of the hardeners and emitters, polymeric UOPs with varying crosslinking density and hydrophobic effect were obtained. Notably, all the polymers show no obvious decrease in UOP emission after high temperature‐humidity test (85°C/85% relative humidity for 7 days). Detailed investigations demonstrate that the rigid covalent crosslinking networks suppress the quenching of triplet excitons while the hydrophobic microenvironment affords good water/moisture‐resistance ability. Moreover, the polymers with superior processability are successfully applied as optical coatings, prepreg, and afterglow displays. With this work, we provide a new strategy to promote the long‐term stability of polymeric UOP materials in high‐temperature‐humidity conditions.